2001
DOI: 10.1007/s100520100673
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order QED corrections to single-W production in electron–positron collisions

Abstract: Four-fermion processes with a particle lost in the beam pipe are studied at lep to perform precision tests of the electroweak theory. Leading higher-order qed corrections to such processes are analyzed within the framework of the Structure Functions (sf) approach. The energy scale entering the qed sf is determined by inspection of the soft and collinear limit of the O(α) radiative corrections to the four-fermion final states, paying particular attention to the process of single-W production. Numerical predicti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For small angle Bhabha scattering and multi-peripheral γ γ processes, where exact QED radiative corrections are already known, the full prediction and the result obtained by using SF at the scale |q 2 γ | are in good agreement [31]. In all other cases, where no exact calculation is available, it has been recently shown that a comparison with the soft limit of the O(α) corrections can determine the scales to be used in SF and PS [32,33]. Detailed analysis, concerning the sensitivity of t-channel scatterings to the choice of the energy scale in the presence of ISR, have been performed [15,32,33], leading to a better understanding of the behaviour of the radiation for single W and γ γ processes.…”
Section: Initial State Radiationmentioning
confidence: 52%
See 1 more Smart Citation
“…For small angle Bhabha scattering and multi-peripheral γ γ processes, where exact QED radiative corrections are already known, the full prediction and the result obtained by using SF at the scale |q 2 γ | are in good agreement [31]. In all other cases, where no exact calculation is available, it has been recently shown that a comparison with the soft limit of the O(α) corrections can determine the scales to be used in SF and PS [32,33]. Detailed analysis, concerning the sensitivity of t-channel scatterings to the choice of the energy scale in the presence of ISR, have been performed [15,32,33], leading to a better understanding of the behaviour of the radiation for single W and γ γ processes.…”
Section: Initial State Radiationmentioning
confidence: 52%
“…WPHACT, grc4f [7], KORALW [12] and COMPHEP [13] are based on Feynman diagrams 1 while NEXTCALIBUR [15] and SWAP [16] are based on the Dyson-Schwinger equations, a set of recursive relations among Green functions. Comparisons between the different codes have shown good technical agreement in several benchmark processes, as recently summarized in [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the second run, for each event use KoralW in order to calculate the correction weight, the bracketed expression in Eq. (12). Optionally, reject the events according to the correction weight.…”
Section: Merge For Fully Exclusive Distributions (Event Per Event)mentioning
confidence: 99%
“…For example KoralW [1,[4][5][6] can generate all four-fermion final states with the fully massive phase space and the complete Born-level four-fermion massive matrix element generated by the GRACE2 package [7]. Apart from KoralW there exists a number of other MC programs for all four-fermion processes at the Born level [8][9][10][11][12][13][14][15][16][17][18][19]. The complete O(α) corrections to the signal e + e − → W + W − → 4f process are implemented only in two MC programs: YFSWW3 [2,[20][21][22][23] and RacoonWW [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…[4] and in ref. [5] More or less, all these attempts amount to start with some sort of naive soft + virtual photon approximation, not the one commonly employed in the Yennie, Frautschi and Suura formalism [6], but rather something as in the following expression:…”
Section: Background Of the Problemmentioning
confidence: 99%